2021
DOI: 10.1101/2021.03.02.433652
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Opposing motors provide mechanical and functional robustness in the human spindle

Abstract: At each cell division, the spindle self-organizes from microtubules and motors. How the spindle's diverse motors, often acting redundantly or in opposition, collectively give rise to its emergent architecture, mechanics, and function is unknown. In human spindles, the motors dynein and Eg5 generate contractile and extensile stress, respectively. Inhibiting dynein or its targeting factor NuMA leads to unfocused, turbulent spindles and inhibiting Eg5 leads to monopoles, yet bipolar spindles form when both are in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…For this reason, we favor a model in which secondary bundles function similarly to bridging fibers and contribute to spindle elongation by interactions with primary microtubule bundles rather than direct interactions with chromosomes (Figure 6B). 65 Similar to results from human cell lines, 35,57,58 the microtubule bundles in Naegleria spindles twist. This observation implies that Naegleria's mitotic microtubule bundles are physically connected, a hypothesis that may explain their regular spacing within the spindle.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…For this reason, we favor a model in which secondary bundles function similarly to bridging fibers and contribute to spindle elongation by interactions with primary microtubule bundles rather than direct interactions with chromosomes (Figure 6B). 65 Similar to results from human cell lines, 35,57,58 the microtubule bundles in Naegleria spindles twist. This observation implies that Naegleria's mitotic microtubule bundles are physically connected, a hypothesis that may explain their regular spacing within the spindle.…”
Section: Discussionmentioning
confidence: 60%
“…The function of spindle chirality in human cells may be a passive mechanical response to spindle forces that decreases the risk of spindle breakage under high load. 58,66 In contrast to the left-handed chirality observed in human cell lines, 35,57,58 the majority of Naegleria spindles are right-handed. When hTERT-RPE1 cells are depleted of components of the key spindle regulator augmin, the spindle twist reverses and becomes right-handed, 58 indicating that the chirality of twist is modulated by microtubule-associated proteins.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Unlike metaphase, in anaphase twist is mostly absent in HeLa and RPE1 spindles. A recent study found strong left-handed twist during anaphase after combined Eg5 inhibition and NuMa depletion in RPE1 cells, suggesting that opposing motors are required to prevent twisting in the anaphase spindle (Neahring et al, 2021).…”
Section: Mechanisms That Generate Spindle Twistmentioning
confidence: 97%
“…The experimentally measured three-dimensional shapes of the microtubule bundles, primarily bridging fibers that laterally link sister kinetochore fibers, were used to deduce forces and torques in the spindle by comparison with a theoretical model (Novak et al, 2018). Lefthanded twist was also observed in spindles lacking NuMA and kinesin-5 activity in RPE1 cells during metaphase and anaphase (Neahring et al, 2021). Another organism whose spindles are prominently twisted is a unicellular eukaryote, amoeba Naegleria gruberi.…”
Section: Introductionmentioning
confidence: 99%